Aminocaproic acid use in hospitalized patients with hematological malignancy: a case series. Issue 3 (2nd February 2015) - Marshall, Ariela; Li, Ang; Drucker, Adrienne; Dzik, Walter
Abstract: The antifibrinolytic aminocaproic acid is widely used in surgical settings to prevent blood loss and decrease transfusion requirements, and small observational studies have suggested that aminocaproic acid may be useful in the setting of malignancy‐related bleeding. At our institution, aminocaproic acid is sometimes prescribed to patients with hematological malignancy who experience refractory thrombocytopenia with or without bleeding. We performed a 5‐year retrospective review of 54 adult patients with 13 types of hematological malignancy who received aminocaproic acid at our institution. Indications for use included 31 (57.4%) for refractory thrombocytopenia with bleeding, 16 (29.6%) for refractory thrombocytopenia without bleeding, and 7 (13%) for bleeding alone. Patients received both oral and intravenous formulations. Administered doses ranged broadly and median duration of use was 6 days. Three patients (5.7%) developed deep venous thrombosis but none of the thrombotic events were clearly related to administration of aminocaproic acid. We conclude that aminocaproic acid may be a relatively safe and cost‐effective adjunct treatment in the setting of bleeding related to the diagnosis and treatment of hematological malignancy. Prospective trials as well as formalized protocols for the use of aminocaproic acid may be indicated. Copyright © 2015 John Wiley & Sons, Ltd.